Factors associated with gabapentin misuse among people who inject drugs in Appalachian Kentucky - Buttram, Mance E. (Subst Use Misuse, 2020)
AIMS: Gabapentin is misused to potentiate the euphoric effects of opioids, self-treat physical pain, and moderate opioid withdrawal symptoms. Because examinations of gabapentin misuse among people who inject drugs (PWID) are scant, the aim of this study is to identify factors associated with gabapentin misuse among this population. METHODS: Data are drawn from a study examining the uptake of syringe service programs (SSPs) in Appalachian Kentucky. The sample includes 324 PWID who were age 18 and over and reported past month drug injection. Logistic regression models were constructed to examine recent (past 90 days) gabapentin misuse. RESULTS: Participants are female (50.0%); Hispanic (2.2%), Black (1.5%), White (90.7%), and other race/ethnicity (4.6%). Mean age is 37. Participants reporting gabapentin misuse had higher odds of reporting misuse of marijuana, cocaine, methamphetamine, prescription opioids, benzodiazepines, prescription stimulants, fentanyl, and buprenorphine (p<.042); severe substance use disorder (p<.000); and recent physical pain (p<.003). In multivariable models, findings related to misuse of prescription opioids and buprenorphine; severe substance use disorder; and recent physical pain or discomfort, remained significant (p<.042). CONCLUSIONS: This is one of the first studies to examine gabapentin misuse among PWID. It is possible that individuals reporting recent gabapentin misuse are attempting to self-treat physical pain when healthcare is limited. Gabapentin may also be misused to achieve desired central nervous system effects and to moderate methamphetamine highs. Syringe service programs can educate PWID about the potential dangers of polydrug use involving gabapentin and to connect PWID with needed healthcare services.